2003
DOI: 10.1016/s0029-7844(03)00360-0
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery velocimetry in patients with gestational hypertension

Abstract: Abnormal uterine Doppler was the variable that was more frequently associated with adverse pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
0
22
1
2
Order By: Relevance
“…Previous studies examining uterine artery PI [29,30,31,32,33] and serum PlGF or the sFlt-1 to PlGF ratio [34,35,36,37,38,39] in the late second or early third trimesters of pregnancy have essentially focused on the investigation of women presenting to specialist clinics with signs of hypertensive disorders with the aim of identifying the subgroup that will develop severe disease [29,30,31,32,33,34]. Our study examined the application of biomarkers in routine screening for subsequent development of PE as part of a strategy for a new approach to prenatal care [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining uterine artery PI [29,30,31,32,33] and serum PlGF or the sFlt-1 to PlGF ratio [34,35,36,37,38,39] in the late second or early third trimesters of pregnancy have essentially focused on the investigation of women presenting to specialist clinics with signs of hypertensive disorders with the aim of identifying the subgroup that will develop severe disease [29,30,31,32,33,34]. Our study examined the application of biomarkers in routine screening for subsequent development of PE as part of a strategy for a new approach to prenatal care [7].…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, Doppler studies were carried out in pregnancies presenting with PE or fetal growth restriction reported that the outcome was worse if there was increased, rather than normal, impedance to flow in the uterine arteries [16,17,18,19,20,21,22]. Similarly, studies investigating pregnancies with abnormal uterine artery Doppler at 20-24 weeks' gestation reported that outcome was worse in those with persistence of high impedance to flow during the third trimester compared to those with normalization in flow [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous uterine artery Doppler studies during the third-trimester examined pregnancies presenting with PE or fetal growth restriction and reported that the outcome was worse if impedance to flow was increased [20,21,22,23,24,25,26]. Two previous screening studies at 30-33 weeks' gestation examined 4,855 pregnancies and reported that at FPR of 5% screening by a combination of maternal characteristics and uterine artery PI or MAP detected 49 and 57%, respectively, of intermediate PE requiring delivery at 34-37 weeks and 37 and 49% of late PE with delivery at ≥38 weeks [27,28].…”
Section: Discussionmentioning
confidence: 99%